Genetic parameters for growth in Charolais calves - Čepon, Marko (Acta agriculturae Slovenica, 2008)
Genetic parameters for birth weight (BW), weight at the beginning (WB), in the middle (WM), and at the end of grazing season (WE), as well as weight at the age of one year (WY) were estimated. Data were collected on 319 Charolais calves. The total number of records, including pedigree data (parents and grandparents) was 377 animals. Variance and covariance components were estimated by REML method using the VCE-5 package. The effects of sex, parity and year of birth were included in the models for all traits. Age of calves at the beginning of grazing season was included as linear regression in models for all traits except for birth weight. The age of calves in the middle, at the end of grazing season, and age at approximately one year were included as linear regression in the models for corresponding weights. Direct additive genetic effect was included in models for all traits as random effect. Estimated heritabilities for BW, WB, WM, WE and WY were 0.62+-0.06, 0.23+-0.09, 0.35+-0.08, 0.29+-0.07 and 0.23+-0.07, respectively.
Keywords: govedo; teleta; pasme; genetski parametri; telesna masa; varianca